2008
DOI: 10.1097/prs.0b013e3181881ffe
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Assessment of Shoulder Morbidity and Recovery Time Scales following Latissimus Dorsi Breast Reconstruction

Abstract: The authors believe this information to be important to the patient, therapist, and surgeon in the assessment of postoperative recovery from this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 10 publications
5
70
3
1
Order By: Relevance
“…Unexpectedly, abduction was not contained in the functions of the LD muscle. In addition, our findings of a significant reduction of ROM in flexion and abduction that remained for 3 years are contradictory to those of some previous reports where shoulder range of motion seemed to recover after surgery despite a decrease in function during the first 6 months [3,4,15]. These discrepancies might be due to the presence or absence of PRT that can increase tissue adhesions.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Unexpectedly, abduction was not contained in the functions of the LD muscle. In addition, our findings of a significant reduction of ROM in flexion and abduction that remained for 3 years are contradictory to those of some previous reports where shoulder range of motion seemed to recover after surgery despite a decrease in function during the first 6 months [3,4,15]. These discrepancies might be due to the presence or absence of PRT that can increase tissue adhesions.…”
Section: Discussioncontrasting
confidence: 84%
“…That reason may be that the LD muscle actively participates most efficiently with the shoulder abduction at more than 90°( 2nd position). Our data indicate that there was no recovery of the weakness after 3 months and contradict other studies that suggested that the other shoulder muscles may be strengthened by the synergistic actions, and the strength seems to return to or near to preoperative values in the second 6-month period after surgery [11,15]. One possible explanation for the discrepancy is that all the patients in our study had PRT.…”
Section: Discussioncontrasting
confidence: 82%
“…These seem to normalize at one year in otherwise unimpaired individuals [26]. Salmi showed that shoulder extension strength deteriorated permanently after part of the latissimus dorsi muscle had been removed even though subjective morbidity was minimal [27].…”
Section: (D) Soft-tissue Reconstructionmentioning
confidence: 99%
“…The surgery is short, the morbidity low, and the functional deficit has been shown to be transient when patients were followed prospectively for 1 year [6]. The flap is indicated mainly for middle posterior defects as its upper reach is limited to the first dorsal vertebrae and wounds of the lumbar area cannot be covered when pedicled on the thoracodorsal vessels.…”
Section: Discussionmentioning
confidence: 99%